Kyoto gardens masterworks of the Japanese gardener's art - Clancy, Judith; Simmons, Ben (Tokyo Rutland, Vermont Tuttle Publishing, 2014)
Kyoto Gardens is a labor of love from master photographer Ben Simmons and Kyoto-based writer Judith Clancy. Simmons' photographs present a fresh and contemporary look at Kyoto's most important gardens. Their beauty is enhanced and humanized by gardeners tending the grounds using the tools of their art. Clancy's graceful text provides historic, aesthetic and cultural context to the gardens. Combining wonder and rigor, she describes how Kyoto's most beloved gardens remain faithful to their founders' creative spirit and conception. Journey to Kyoto's thirty gardens with just a turn of a page, or use the handy maps to plan your trip.
Reshaping the land -- Gardens of central and eastern Kyoto -- Gardens of northern Kyoto -- Gardens of western Kyoto -- Gardens of southern Kyoto.
Keywords: Gardens, Japanese -- Japan -- Kyoto -- Pictorial works; Gardens, Japanese -- Pictorial works; Japan -- Kyoto